Projeto de uma linha de distribuição de ar-comprimido: estudo de caso do laboratório de ensino no curso de engenharia de produção - (:unkn) unknown (Universidade Federal do Pampa, 2015)
The Industrial Automation, to be increasingly present in both industrial plants and in our daily lives, making people's lives, whether in a manufacturing process in which machines are to perform repetitive tasks that were previously done by workers; is providing comfort in personal and home-use systems, such as we access bank accounts through mobile, to program an alarm system or simply trigger-grinders electronic gates. Commonly used as an energy source to drive the automation of industrial machinery, compressed air, through the principles of pneumatics, has become a smart and cost effective option. This study aims to design a compressed air distribution line for use in Production Engineering Course laboratories of the Federal University of Pampa (UNIPAMPA) campus Bage, RS, which has two laboratories that rely on compressed air line to supply their equipment: the Industrial Automation Laboratory and Metrology Laboratory - Lamet. The methodology used in the development of the work is of quantitative character, being delineated as a case study, which seeks a thorough study of one or a few objects. At the end of this study, we present the design of a compressed air distribution network, showing the total flow needed to supply this equipment in laboratories, the design and layout of the compressed air network.
Keywords: Engenharia; Engenharia de produção; Automação; Pneumática; Rede de ar-comprimido; CNPQ::ENGENHARIAS